Understanding congested travel in urban areas - Serdar Çolak (Nature Portfolio, 2016)
Rapid urbanization burdens urban road infrastructures, but understanding the interplay of road infrastructure and travel patterns is a complex challenge. Here, authors use mobile phone traces during morning peak hours to evaluate the effect of a congestion relief approach under a centralized routing scheme.